Biquaternionic Reformulation of a Fractional Monochromatic Maxwell System - Yudier Peña Pérez; Ricardo Abreu Blaya; Martín Patricio Árciga Alejandre; Juan Bory Reyes (Advances in High Energy Physics)
In this work, we propose a biquaternionic reformulation of a fractional monochromatic Maxwell system. Additionally, some examples are given to illustrate how the quaternionic fractional approach emerges in linear hydrodynamics and elasticity.